Senescence in Bacteria and Its Underlying Mechanisms - Steiner, Ulrich Karl (Frontiers in Cell and Developmental Biology, 2021)
Bacteria have been thought to flee senescence by dividing into two identical daughter cells, but this notion of immortality has changed over the last two decades. Asymmetry between daughter cells after binary fission is revealed in physiological function, cell growth, and survival probabilities, and is expected from theoretical understanding. Since the discovery of senescence in morphological identical, but physiological asymmetric, dividing bacteria, mechanisms of bacteria aging have been explored across levels of biological organization. Quantitative investigations are heavily biased towards E. coli and on the role of inclusion bodies, clusters of misfolded proteins. Despite intensive efforts, to date it is not evident if and how inclusion bodies, a phenotype linked to the loss of proteostasis and one of the consequences of a chain of reactions triggered by reactive oxygen species, contributes to senescence in bacteria. Recent findings in bacteria question that inclusion bodies are only deleterious. Contributions of other hallmarks of aging, identified for metazoans, remain elusive. For instance, genomic instability, appears to be age independent, epigenetic alterations might be little age-specific, and other hallmarks should not play a major role in bacteria systems. What surprises is, that on the one hand classical senescence patterns, such as an early exponential increase in mortality followed by late age mortality plateaus are found, but, on the other hand, identifying mechanisms that link to these patterns are challenging. Senescence patterns are sensitive to the environmental conditions and to the genetic background, even within species, which suggests diverse evolutionary selective forces on senescence that go beyond generalized expectations of classical evolutionary theories of aging. Given the molecular tool kids available in bacteria, the high control of experimental conditions, the high-throughput data collection using microfluidic systems, and the ease of life-cell imaging of fluorescently marked transcription, translation, and proteomic dynamics, in combination with the simple demographics of growth, division and mortality of bacteria, make the challenges experienced surprising. The diversity of mechanisms and patterns revealed, and their environmental dependencies faces us not only with challenges, but also opens exciting opportunities for discovery and deeper understanding of aging and its mechanisms, maybe beyond bacteria and aging.